Peran Program Makan Bergizi Gratis Terhadap Peningkatan Status Gizi dan Tingkat Kesukaan Makanan Penerima Manfaat di Kabupaten Majalengka Jawa Barat - Rachmawati, Ike; Azizah, Dawia Nur; Sutisna, Ateng (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2026)
This study was conducted in response to the still-found cases of elementary school students experiencing limited balanced nutritional intake due to inadequate daily packed meals and the habit of eating random snacks, which negatively impact physical condition and learning concentration in the classroom. The Free Nutritious Meal Program (MBG) emerges as a school-based nutritional intervention expected to systematically address these issues. This study aims to analyze the role of MBG in improving nutritional status and food preference levels among beneficiary students. The study employed a qualitative approach with a case study design, conducted through in-depth interviews with the school principal and classroom teachers, as well as document review comprising school health records and daily food distribution reports. The results revealed various positive changes observed in students, including stable weight gain of approximately 1–2 kg based on routine school records, fresher and more energetic facial appearance, reduced complaints of hunger and dizziness before dismissal time, and improved attendance rates due to students falling ill with fever or flu less frequently. The scheduled group dining atmosphere supervised by teachers made students more disciplined and enthusiastic in enjoying the daily menu consisting of rice, vegetables, protein side dishes such as chicken or egg, and fresh fruits, so that consumption of nutritious food became more routine and the level of preference toward various types of food increased significantly. The study concludes the MBG program plays a meaningful role in improving nutritional status both behavior.